Hubungan resesi gingiva dengan metode menyikat gigi horizontal dan vertikal pada lansia - Stephanie Stephanie; Idamawati Nababan (Prima Journal of Oral and Dental Sciences, 2019)
The tooth brushing technique that is often done inappropriately is the horizontal and vertical tooth brushing technique. This study was conducted to determine the relationship of gingival recession with horizontal and vertical tooth brushing methods in the elderly  at the Karya Kasih Nursing Home in Medan. The severity of gingival recession based on Marini was also measured and assessed as follows: mild recession less than or equal to three millimeters (≤ 3mm) from exposed root surfaces, Moderate gingival recession: three to four millimeters (3- 4mm) from exposed root surfaces, severe gingival recession: more than four millimeters (4mm) from the exposed root surface. To determine the relationship of gingival recession with the tooth brushing method, direct observation and examination of the oral cavity were carried out. The average analysis was carried out by chi square test with SPSS software. The total sample of 20 people who used the horizontal tooth brushing method, mild gingival recession 1 person (5%), moderate gingival recession severity 5 people (25 %), severe gingival recession severity 14 people (70%), whereas No one experienced mild severity with a vertical tooth brushing method, moderate recession severity 2 people, severe gingival recession severity of 18 people (90%). The results of the Chi-Square Test statistical analysis showed that there were no significant differences between the horizontal and vertical tooth brushing methods in the elderly at the Medan Kasih Kasih Nursing Home (p = 0.325, p >0.05).